Pertanggungjawaban Pidana pada Tindak Pidana Persetubuhan terhadap Korban Anak (Studi Kasus Polres Semarang): Penelitian - Arlina Azzahra; Arista Candra Irawati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The act of engaging in sexual intercourse with a child is a serious offense that inflicts long-term psychological and social damage on the victim. In Indonesia’s criminal justice framework, offenders may be subjected to strict legal consequences, as outlined in Law Number 35 of 2014 on Child Protection and the Indonesian Penal Code (KUHP). This study seeks to analyze the form of criminal accountability applied to offenders and identify the barriers faced in enforcing legal regulations surrounding child sexual abuse. The study finds that, although the legal framework is in place, its application continues to face critical obstacles. Thus, reinforcing the child protection system and enhancing cooperation among stakeholders is vital to delivering meaningful justice for child victims.